The Crotoxin:SBA-15 Complex Down-Regulates the Incidence and Intensity of Experimental Autoimmune Encephalomyelitis Through Peripheral and Central Actions - Sant'Anna, Morena Brazil; Giardini, Aline C.; Ribeiro, Marcio A. C.; Lopes, Flavia S. R.; Teixeira, Nathalia B.; Kimura, Louise F.; Bufalo, Michelle C.; Ribeiro, Orlando G.; Borrego, Andrea; Cabrera, Wafa H. K.; Ferreira, Julio C. B.; Zambelli, Vanessa O.; et al. (Frontiers in Immunology, 2020)
Crotoxin (CTX), the main neurotoxin from Crotalus durissus terrificus snake venom, has anti-inflammatory, immunomodulatory and antinociceptive activities. However, the CTX-induced toxicity may compromise its use. Under this scenario, the use of nanoparticle such as nanostructured mesoporous silica (SBA-15) as a carrier might become a feasible approach to improve CTX safety. Here, we determined the benefits of SBA-15 on CTX-related neuroinflammatory and immunomodulatory properties during experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis that replicates several histopathological and immunological features observed in humans. We showed that a single administration of CTX:SBA-15 (54 μg/kg) was more effective in reducing pain and ameliorated the clinical score (motor impairment) in EAE animals compared to the CTX-treated EAE group; therefore, improving the disease outcome. Of interest, CTX:SBA-15, but not unconjugated CTX, prevented EAE-induced atrophy and loss of muscle function. Further supporting an immune mechanism, CTX:SBA-15 treatment reduced both recruitment and proliferation of peripheral Th17 cells as well as diminished IL-17 expression and glial cells activation in the spinal cord in EAE animals when compared with CTX-treated EAE group. Finally, CTX:SBA-15, but not unconjugated CTX, prevented the EAE-induced cell infiltration in the CNS. These results provide evidence that SBA-15 maximizes the immunomodulatory and anti-inflammatory effects of CTX in an EAE model; therefore, suggesting that SBA-15 has a potential to improve CTX effectiveness in the treatment of MS.